Conservação preventiva em contextos culturais : recursos tecnológicos para gestão de risco ambiental; poluição - Homem, Paula Menino (2014)
This paper aims to a commented dissemination of some strategies and resources useful to integrated risk management for cultural heritage, raising awareness of the synergistic relationships between different environmental parameters, but focusing attention on indoor pollution.